2019
DOI: 10.3390/genes10060459
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Impact of Seven Missense Variants of Phenylalanine Hydroxylase

Abstract: The molecular genetics of well-characterized inherited diseases, such as phenylketonuria (PKU) and hyperphenylalaninemia (HPA) predominantly caused by mutations in the phenylalanine hydroxylase (PAH) gene, is often complicated by the identification of many novel variants, often with no obvious impact on the associated disorder. To date, more than 1100 PAH variants have been identified of which a substantial portion have unknown clinical significance. In this work, we study the functionality of seven yet unchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…There have been identified PAH 1101 variants in PAHvdb Database; 6 about 50% are missense mutations. 7 Gu et al (2014) suggested that mutations in the PAH gene consist of 13,5% deletions, 1.8% insertions, 5% nonsense, 60.5% missense, and 11% splice site, (Pecimonova et al, 2019) . The p.Arg408Trp is the most common mutation in many populations, 2 Gundorova et al (2019) suggested that the pathogenic variant p.Arg408Trp is widespread in Europe.…”
Section: The Pah Genementioning
confidence: 99%
“…There have been identified PAH 1101 variants in PAHvdb Database; 6 about 50% are missense mutations. 7 Gu et al (2014) suggested that mutations in the PAH gene consist of 13,5% deletions, 1.8% insertions, 5% nonsense, 60.5% missense, and 11% splice site, (Pecimonova et al, 2019) . The p.Arg408Trp is the most common mutation in many populations, 2 Gundorova et al (2019) suggested that the pathogenic variant p.Arg408Trp is widespread in Europe.…”
Section: The Pah Genementioning
confidence: 99%
“…There have been identified PAH 1101 variants in PAHvdb Database; 6 about 50% are missense mutations. 7 Gu et al (2014) suggested that mutations in the PAH gene consist of 13,5% deletions, 1.8% insertions, 5% nonsense, 60.5% missense, and 11% splice site, (Pecimonova et al, 2019) . The p.Arg408Trp is the most common mutation in many populations, 2 Gundorova et al (2019) (Gundorova et al, 2019).…”
Section: Genes In Phenylketonuriamentioning
confidence: 99%
“…Liver and kidney are the main organs that excrete the PAH enzyme [9,10]. The deficiency of PAH enzyme leads to the accumulation of phenylalanine (Phe) amino acid in the blood, causing phenylketonuria (PKU), a disease that causes mental retardation in infants and children [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%